Peritonitis due to Penicillium and Enterobacter in a patient receiving continuous ambulatory peritoneal dialysis - Böhlke,Maristela (2007)
Infectious peritonitis is a common complication of continuous ambulatory peritoneal dialysis (CAPD). Polymicrobial peritonitis accounts for about 8% of the peritonitis episodes and involves fungi in 9% to 33% of cases. We report the known first case of polymicrobial peritonitis in which Penicillium sp. was one of the organisms cultured and the ninth case of Penicillium peritonitis in CAPD.